The Driving Lesson as a Socio-Technical Situation. A Case Study on the Interaction between Learner Driver, Driving Instructor, and the Motor Car - Schmidl, Alexander (Qualitative Sociology Review, 2021)
A micro-sociological examination of the driving lesson raises the following question: How is the interaction between learner driver and driving instructor structured in this technical setting, and what meaning can be ascribed in this threefold constellation to the vehicle with its various technical elements? This case study examines the orientation patterns which exist between the learner driver, the driving instructor, and the car, which together constitute a socio-technical triangle, and what actions the learner driver needs to learn to enable them to drive the car safely. The theoretical background to the study is provided by interactionist theories, which have been broadened to include a greater sensitivity for the body and technology, and a sociological reading of postphenomenology. Using a method based on this theoretical background and informed by workplace studies, this study observed and made audiovisual recordings of driving lessons. This approach made it possible to undertake a detailed analysis of the situations, reveal how the human body interacts with technology, and how a person’s attention responds to technical information. In these situations, the driving instructor takes on the role of the translator by mediating between various situational definitions—one’s own, that of the inexperienced learner driver, other motorists, and the driver assistance systems in the car. The driving instructor represents the driving school as an institution that is responsible for creating an intersubjectively arranged understanding of how to deal with technology and socio-technical situations.